2015
DOI: 10.1177/0271678x15606460
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoxia increases the cerebral metabolic rate – a magnetic resonance imaging study

Abstract: The aim of the present study was to examine changes in cerebral metabolism by magnetic resonance imaging of healthy subjects during inhalation of 10% O2 hypoxic air. Hypoxic exposure elevates cerebral perfusion, but its effect on energy metabolism has been less investigated. Magnetic resonance imaging techniques were used to measure global cerebral blood flow and the venous oxygen saturation in the sagittal sinus. Global cerebral metabolic rate of oxygen was quantified from cerebral blood flow and arteriovenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 42 publications
7
67
6
Order By: Relevance
“…Several recent MRI studies have all suggested a moderate increase of CMRO 2 due to hypoxia. 2,40,48 In this regard, the observation in the present study is in good agreement with these prior findings. It is still unclear what the physiological mechanism is that could explain the elevated brain oxygen metabolic rate during hypoxic state.…”
Section: 34supporting
confidence: 93%
See 1 more Smart Citation
“…Several recent MRI studies have all suggested a moderate increase of CMRO 2 due to hypoxia. 2,40,48 In this regard, the observation in the present study is in good agreement with these prior findings. It is still unclear what the physiological mechanism is that could explain the elevated brain oxygen metabolic rate during hypoxic state.…”
Section: 34supporting
confidence: 93%
“…These values are with the typical range of the literature reports. 1,2,12,18,[35][36][37][38][39][40][41][42] But the effect of gas modulation on neural or metabolic activity is not fully understood and is in fact still controversial. This is primarily due to a lack of tools to examine these questions, because one can no longer use vascular surrogate marker (for which plenty of tools are available) and must use direct assessment of neural activity or metabolic rate.…”
Section: 34mentioning
confidence: 99%
“…S6), including decreased r s a O 2 (79±7% of the baseline value measured under normoxia) and increased rOEF (148±14%), rCBF total (141±40%), and rCMRO 2 (156±21%). These observations in the hypoxic mouse brain nicely echoed a recent human study using magnetic resonance imaging (Vestergaard et al, 2016). …”
Section: Resultssupporting
confidence: 76%
“…Cerebral OEF is inversely proportional to CBF when metabolism is held constant, and directly proportional to metabolism when CBF is held constant, consistent with the conservation of (O 2 ) mass principle. The effects of acute hypoxia on CMRO 2 are minimal, with reports of slight (5-8.5%) increases (Xu et al 2012;Vestergaard et al 2015) or no changes (Kety & Schmidt, 1948;Cohen et al 1967;. Differences in measurement techniques and the degree of hypoxia and/or CO 2 control might explain these small differences.…”
Section: Cerebral Oxygen Delivery Flow Extraction and Metabolismmentioning
confidence: 99%
“…For example, recent animal studies have reported that brainstem parenchymal P O 2 is ß60 mmHg lower than P aO 2 even during normoxia (Marina et al 2015). At least during periods of acute (40 min) exposure to poikilocapnic hypoxia (fractional inspired O 2 of 0.10), however, a recent human-based magnetic resonance proton spectroscopy study reported small elevations in CBF and CMRO 2 (ß8%) and reductions in creatine and phosphocreatine concentrations of ß15% (Vestergaard et al 2015). The authors speculated that a shift towards creatine-mediated ATP catalysis as a manifestation of hypoxia could reflect a defence mechanism.…”
Section: Hypoxic Vasodilatationmentioning
confidence: 99%